2007
DOI: 10.1016/s1808-8694(15)30105-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of patients harboring temporomandibular disorders in an otorhinolaryngology departament

Abstract: The prevalence of temporomandibular disorders was 21.72%, being significantly higher among female subjects (p:0.0001). The prevalence regarding the indexes, was: TMD absent: 37.56%; mild TMD: 40.72%; moderate TMD 19% and severe TMD: 2.72%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 17 publications
(12 reference statements)
0
6
0
9
Order By: Relevance
“…28 There are many studies on the prevalence of TMD in different age groups. [29][30][31] However, studies evaluating prevalence of TMD in the elderly are scares; and most of them are not about institutionalized, but about community-dwelling ones. 5,6,[32][33][34] One study has shown an interesting prevalence of TMD symptoms when comparing institutionalized and communitydwelling elders.…”
Section: Discussionmentioning
confidence: 99%
“…28 There are many studies on the prevalence of TMD in different age groups. [29][30][31] However, studies evaluating prevalence of TMD in the elderly are scares; and most of them are not about institutionalized, but about community-dwelling ones. 5,6,[32][33][34] One study has shown an interesting prevalence of TMD symptoms when comparing institutionalized and communitydwelling elders.…”
Section: Discussionmentioning
confidence: 99%
“…Entre os diversos sinais e sintomas, os principais são dor na região orofacial, dificuldade de movimentar a mandíbula, ruído ou estalido na articulação, e sensibilidade na musculatura 2,[11][12][13][14] . As alterações da DTM desencadeiam dor na musculatura da face, deslocam o disco articular, provocam dor na articulação e alteração da função, podendo causar inflamação.…”
Section: Disfunção Temporomandibularunclassified
“…Promovendo assim limitações físicas e funcionais aos portadores 15 . Dentre os diversos sinais e sintomas apresentados pela DTM a dor é a que mais interfere nas atividades diárias do indivíduo, ocasionando um efeito negativo na vida social, emocional, e nível energético da pessoa afetada 14 .…”
Section: Disfunção Temporomandibularunclassified
See 1 more Smart Citation
“…Neste estudo não foi possível observar diferença em sinais e sintomas de DTM entre os sexos femininos e masculinos pelo tamanho da amostra, porém estudos apontam maior prevalência de DTM em pessoas do sexo feminino, na proporção de 4:1 (ÖZAN et al, 2007;POVEDA RODA et al, 2007;SILVEIRA et al, 2007).…”
Section: Gráfico 7: Dor à Palpação Muscular Extra-oral No Músculo Estunclassified